The Relationship between the Supervision Role and Compassion Fatigue and Burnout in Genetic Counseling. Issue 6 (19th May 2016) - Allsbrook, Katlin; Atzinger, Carrie; He, Hua; Engelhard, Chalee; Yager, Geoffrey; Wusik, Katie
Abstract: Many genetic counselors provide supervision to students during their career. Previous studies have shown genetic counselors, in general, are at increased risk for developing compassion fatigue. The purpose of this study was to determine if there was a difference in compassion fatigue and burnout levels in genetic counselors who currently supervise compared to genetic counselors who do not. Genetic counselors who currently practice in a clinical setting ( N = 391) completed an online survey containing demographic questions, the Professional Quality of Life Scale, the State‐Trait Anxiety Inventory, and questions specific to the genetic counselor's experiences with supervision. Overall, when controlling for trait‐anxiety, the supervision role by itself was not independently associated with the risk for compassion fatigue and burnout among genetic counselors. Within supervisors, however, there were several factors which were associated with this risk. Those with less supervision experience reported more secondary traumatic stress. Those supervisors reporting less confidence had decreased compassion satisfaction. Those with less experience or less confidence in their supervision role were most likely to be at increased risk for developing compassion fatigue. Training in supervision and support for dealing with compassion fatigue and burnout may be beneficial to supervisors with less experience.